Mechanically durable tri-composite polyamide 6/hematite nanoparticle/tetra-n-butylammonium bromide (PA6/α-Fe2O3/TBAB) nanofiber based membranes for phosphate remediation - Choi, Yun Young; Hanh To, Dung Thi; Kim, Sewoon; Cwiertny, David M.; Myung, Nosang V. (Frontiers in Chemistry, 2024)
Essential properties for a Point of Use (POU) water filter include maintaining high removal capacity and rate, with excellent mechanical properties to withstand pressure drop. Herein, mechanically robust tri-composite polyamide 6/iron oxide nanoparticles/tetra-n-butylammonium bromide (PA6/α-Fe2O3/TBAB) nanofiber composite membranes were electrospun for phosphate (P) remediation, where the diameter and composition were tuned by controlling solution compositions and electrospinning conditions. Tri-composite composition and morphology affect phosphate uptake where the adsorption capacity followed Langmuir isotherm whereas the adsorption kinetics followed pseudo second order behavior. Mechanical properties (i.e., Young's Modulus (E) and toughness) were significantly influenced by the composition and morphology of the tri-composite, as well. Although additional TBAB and iron oxide decreased toughness, there are optimum composition ranges which resulted in maximum Young's Modulus. Of the synthesized nanofiber membranes, PA6/α-Fe2O3/TBAB nanofibers with 17% α-Fe2O3 and 2% TBAB showed excellent phosphate uptake capacity (i.e., 8.9 mg/g (52 mg of P/g of α-Fe2O3)) while it is bendable, stretchable, and able to plastically deform without fracturing (i.e., Young's modulus of 2.06× 10 8 Pa and Toughness of 1.35 × 10 6 J m -3 ). With concerns over the impact of P on water resources and the long-term availability of limited P resources, this tri-composite membrane is well suited for applications in both wastewater treatment and resource recovery.